2011
DOI: 10.3109/08958378.2011.575413
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the pathological response and fate in the lung and pleura of chrysotile in combination with fine particles compared to amosite-asbestos following short-term inhalation exposure

Abstract: The marked difference in biopersistence and pathological response between chrysotile and amphibole asbestos has been well documented. This study is unique in that it has examined a commercial chrysotile product that was used as a joint compound. The pathological response was quantified in the lung and translocation of fibers to and pathological response in the pleural cavity determined. This paper presents the final results from the study. Rats were exposed by inhalation 6 h/day for 5 days to a well-defined fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…For all fibers lengths there was no subsequent clearance and the clearance half-time was estimated as greater than 1000 days. In previous biopersistence studies with amphibole asbestos, the clearance half-time was reported to range from 418 to N1000 days (Musselman et al, 1994;Hesterberg et al, 1996Hesterberg et al, , 1998Bernstein et al, 2005bBernstein et al, , 2011.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…For all fibers lengths there was no subsequent clearance and the clearance half-time was estimated as greater than 1000 days. In previous biopersistence studies with amphibole asbestos, the clearance half-time was reported to range from 418 to N1000 days (Musselman et al, 1994;Hesterberg et al, 1996Hesterberg et al, , 1998Bernstein et al, 2005bBernstein et al, , 2011.…”
Section: Discussionmentioning
confidence: 97%
“…Chrysotile can vary in characteristic depending upon the mine and processing of the ore. In earlier studies of chrysotile alone or of chrysotile mixed with a joint compound (Bernstein et al, 2003(Bernstein et al, , 2004(Bernstein et al, , 2005a(Bernstein et al, , 2005b(Bernstein et al, , 2008(Bernstein et al, , 2011 the clearance half-time of the longer fibers ranged from 0.7 to 11.4 days. The lack of a fiber related response in the histopathological findings in either the lung or the pleural cavity strongly suggests that the few (group 2: 6.5-10 fibers counted on the filter; group 3: 1-5 fibers counted on the filter) remaining fibers longer than 20 μm in the current study were in the airways and not in the parenchyma.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Asbestos occurs in two mineralogic forms: commercially used amphiboles (e.g., commercially available amosite and crocidolite) and chrysotile. Amosite and crocidolite are considerably more persistent in tissue than is chrysotile, which disappears from lung tissue rapidly (Bernstein et al, 2005, 2010, 2011). This difference in biopersistence is believed to be the one of reasons that mesothelioma incidence rates are much higher in those who used or manufactured products with amosite and crocidolite, when compared to those exposed to only chrysotile (Churg, 1998; Hodgson and Darnton, 2000; Yarborough, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…32 Animal investigations have also demonstrated long commercial amphibole fibers directly penetrating the visceral pleura and extending into the pleural space. 33 …”
mentioning
confidence: 99%